2010
DOI: 10.1007/s10695-010-9403-x
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein biosynthesis as a detoxification mechanism in mercury exposure in fish, spotted scat (Scatophagus argus)

Abstract: It is of crucial importance to study on the biomarkers types to assess the specification of the pollutants and health status of marine ecosystems in environmental evaluation projects. In this respect, total metallothionein biosynthesis and mercury bioaccumulation in the liver and gills under acute mercury exposure were investigated in fish, Scat (Scatophagus argus). Spotted scat was exposed to different mercury concentrations (0, 10, 20, 30) for 24, 48, 72 h. Total MT levels were determined by enzyme-linked im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…The pattern of MT content in the tissues was in the decreasing order of: liver > gills > muscle.This result confirms earlier studies. The highest concentration of MT seen in the liver, is in accordance with the findings of some authors such as Tom et al [22] and Sinaie et al [60] who reported highest concentrations of MT in liver while lowest average MT was reported in muscle of Colossoma macropomum by Lemus et al [39]. High levels of copper in the liver was ascribed to copper binding to MT, which serves as a detoxification mechanism [61].…”
Section: Mt Levels In the Tissues Of Mudskipper P Schlosserisupporting
confidence: 85%
“…The pattern of MT content in the tissues was in the decreasing order of: liver > gills > muscle.This result confirms earlier studies. The highest concentration of MT seen in the liver, is in accordance with the findings of some authors such as Tom et al [22] and Sinaie et al [60] who reported highest concentrations of MT in liver while lowest average MT was reported in muscle of Colossoma macropomum by Lemus et al [39]. High levels of copper in the liver was ascribed to copper binding to MT, which serves as a detoxification mechanism [61].…”
Section: Mt Levels In the Tissues Of Mudskipper P Schlosserisupporting
confidence: 85%
“…Fish have been often used as appropriate bioindicators of chemical contaminants (Sinaie et al 2010;Tolosa et al 2005;Zuloaga et al 2009). Under conditions of stress, the body of the fish emits immediate responses recognized as primary and secondary responses.…”
mentioning
confidence: 99%
“…The plot for Hg in Figure 6 hints at seasonal differences in liver Hg levels at Kafue Flats and Kafue Town, with a trend towards lower levels in the warm-rainy season. Mercury exposure leading to MT induction has been observed previously [ 124 , 125 , 126 ]. Whilst the average values did not display statistically significant differences, it appears possible that small seasonal variations in Hg levels may be contributing to MT induction levels, and this trend should be followed up in the future.…”
Section: Resultsmentioning
confidence: 89%